Post Traumatic Cerebellar Ataxia – A Least Pondered Diagnosis: A Case Report - Shobana, Sridhar; Revathi, Krishnakumar; Kumar, Thirunavukkarasu Bharath (Journal of Nepal Paediatric Society, 2022)
Ataxia means impaired co-ordination of voluntary muscle movement. It is a physical finding, not a disease and the underlying etiology needs to be investigated. It can be the patient’s presenting complaint or a component among other presenting symptoms. Cerebellar dysfunction or impaired vestibular or proprioceptive input to cerebellum can cause ataxia. Though there are several etiologies post infectious ataxia is the most common one in children. But other rare etiologies of ataxia should also be considered based on the clinical presentation. We try to emphasise on this point by presenting a case of post traumatic cerebellar ataxia – a rare entity in children.